Profile of sales and notifications of suspected adverse events related to hydroxychloroquine and chloroquine during the COVID-19 pandemic (Research, Society and Development, 2023)
The goal of this study is to describe the profile of hydroxychloroquine sales and reports of suspected adverse events related to chloroquine and hydroxychloroquine during the COVID-19 pandemic. This is a descriptive study which data were extracted from the Industrialized Drug Sales Panel and the Pharmacovigilance Notification Panel. The results show that 1.862.978 boxes of hydroxychloroquine were sold in the period of April 01,2020 to August 31,2021, with an average of 109.586 boxes sold per month (median=110.318; minimum=72.042; maximum=187.752). Also, 1.064 notifications involving chloroquine or hydroxychloroquine were realized in the period of March 01,2020 to August 31, 2021 and more than half of them (n=617.57.8%) were documented by June 2020, while only 40 were recorded in January/2021 to August/2021. These findings were correlated with scientific evidence, as in vitro and preliminary studies, published at the beginning of the pandemic, found important results regarding the use of these medications to treat COVID-19. However, in mid-2020, more robust studies indicated that these agents were not effective in treating or preventing COVID-19, and to being unsafe for the patient. Consequently, the use of these drugs in Brazilian hospitals had declined. This fact justified the reduction of notifications involving these drugs, since the detection and notification of adverse events often occur in the hospital environment, where the patient is constantly monitored. Despite the evidence that hydroxychloroquine is not effective to prevent/treat COVID-19, the sales profile remained high during the period evaluated indicating how the social and political incentive influenced Brazilians to use these medications.